Cutaneous complications in diabetes mellitus: pathophysiology, clinical relevance and the role of physical activity in prevention – a literature review - Kulasza, Paulina Sara; Kalinowska, Weronika; Szczepański, Michał; Dzieszko, Natalia; Borowski, Maciej; Szeliga, Aleksandra; Ksiazek, Tomasz Karol; Dembicki, Piotr Mikolaj; Francuziak, Anna Ewelina; Kozlowska, Kinga (Quality in Sport, 2025)
Diabetes mellitus is a chronic metabolic disease leading to a number of complications, including skin lesions, which may be the first sign of hyperglycaemia or indicative of advanced disease. In recent years, increasing attention has been paid to the role of physical activity not only in improving glycaemic control, but also in reducing the pathophysiological processes responsible for the cutaneous manifestations of diabetes. The aim of this study was to present the most common cutaneous lesions in patients with diabetes, their mechanisms of formation and to assess the impact of physical activity on their occurrence and course.